Protecting emergency responders : lessons learned from terrorist attacks - Jackson, Brian A., 1972- (Conference proceedings (Rand Corporation) ;, 2002)
Based on a 2001 conference held in New York City that looked at ways of improving health and safety for emergency workers who respond to terrorist attacks. It is intended for managers and decisionmakers to help them understand the working and safety environment associated with such attacks.